1974
DOI: 10.1090/s0002-9939-1974-0350310-6
|View full text |Cite
|
Sign up to set email alerts
|

On the a.e. convergence of Walsh-Kaczmarz-Fourier series

Abstract: Abstract.It is shown that partial sums of Walsh-KaczmarzFourier series of functions in the Orlicz class L(log+ L)2 converge a.e. The proof utilizes an estimate of P. Sjölin on the partial sums of the usual Walsh-Fourier series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 6 publications
0
14
0
1
Order By: Relevance
“…In 2008 Goginava [8] proved that the maximal operatorσ * In 1948 Šneider [16] introduced the Walsh-Kaczmarz system and showed that the inequality lim sup n→∞ D κ n (x) log n C > 0 holds a.e. In 1974 Schipp [12] and Young [18] proved that the Walsh-Kaczmarz system is a convergence system. Skvortsov in 1981 [15] showed that the Fejér means with respect to the Walsh-Kaczmarz system converge uniformly to f for any continuous function f .…”
Section: Introductionmentioning
confidence: 99%
“…In 2008 Goginava [8] proved that the maximal operatorσ * In 1948 Šneider [16] introduced the Walsh-Kaczmarz system and showed that the inequality lim sup n→∞ D κ n (x) log n C > 0 holds a.e. In 1974 Schipp [12] and Young [18] proved that the Walsh-Kaczmarz system is a convergence system. Skvortsov in 1981 [15] showed that the Fejér means with respect to the Walsh-Kaczmarz system converge uniformly to f for any continuous function f .…”
Section: Introductionmentioning
confidence: 99%
“…In 1974, Schipp [2] and Young [3] proved that the Walsh-Kaczmarz system is a convergence system. In 1981, Skvortsov [4] showed that the Fejér means with respect to the Walsh-Kaczmarz system converge uniformly to f for any continuous function f. Gát [5] proved that, for any integrable function, the Fejér means with respect to the Walsh-Kaczmarz system converge almost everywhere to this function and, furthermore,…”
Section: Introductionmentioning
confidence: 99%
“…В работе [2] показано, что для всякой функции из класса (ln + ) 2 [0, 1] ее ряды Фурье-Уолша-Качмажа сходятся к ней почти всюду. Для тригонометрической системы и систе-мы Уолша-Пэли аналогичный результат для класса ln + ln + ln + ln + [0, 1] полу-чен Антоновым в [3] и [4], а также независимо Сьелином и Сориа для системы Уолша-Пэли в [5].…”
Section: Doi: 104213/mzm4509unclassified